International Anti-Corruption Standards and Russian Criminal Code - O. I. Lepeshkina (Теоретическая и прикладная юриспруденция)
This article describes history and contemporary status anti-corruption standards in the international community of states, universal and regional. There is analysis about execution of Russian Federation it’s international obligations on against corruption in this article. Considerable changes in Criminal Code about responsibility for corruption crimes are made after ratifi cation Criminal Law Convention on Corruption. Russia is successfully executed three evaluation rounds of GRECO on anti-corruption legislation. The aggravating circumstances of petty bribery are made by author in the article. Moreover, it is necessary to eliminate the error in article 291.2 regarding imposition of punishment in the form of correctional labour, made when imposing sanctions for petty bribery.